Investigations on composite deck with different interface connections - Meroola, Vakil; Harshvadan, Patel; Mevada, Kalpit (Journal of Structural Engineering, 2025)
Profile steel sheet concrete composite slab are gaining increasing usage in modern construction practice in many parts of world. But in India, composite deck construction is an emerging concept. Load carrying capacity of composite deck is associated with bond between steel and concrete, which is generally provided by embossment. Role of embossment, its standard dimensions and its ability to transfer horizontal shear for various profile configuration is not much explored in Indian context. Moreover, for each profile configuration and embossment pattern separate set of full scale testing is necessary. This paper focuses on innovative bond techniques as an alternative to embossments in profile sheets by relatively small scale test. A total of twelve composite specimens, each in set of two specimens are casted and tested under uniformly distributed load with varying interface connections. The connection patterns considered are: bolt with different orientation, semicircular bend and bolt combination, stiffener and fabricated embossment. Comparison of load carrying capacities from the tests is presented. Comparison of test result has been made and it is found that connection topology with semicircular bend and bolt combination performed better in terms of load carrying capacity than other topologies.